Dampak Kebijakan Moneter Sanering oleh Pemerintah Republik Indonesia Terhadap Kondisi Sosial-Ekonomi Masyarakat, 1965-1970 - Ramadhan, Fauzan Syahru; Daradjati, Keke Pahlevi; Nugroho, Khairana Zata (Jurnal Pattingalloang, 2025)
The article entitled “The Impact of the Sanering Monetary Policy by the Government of the Republic of Indonesia on the Socio-Economic Conditions of Society during 1965-1970” reveals the process of issuing and implementing the sanering monetary policy, as well as the impact of the sanering monetary policy on the socio-economic conditions of society in 1965-1970. This study uses historical methods including heuristics, criticism, interpretation and historiography presented in analytical-descriptive form. The results of this research explain that during the Guided Democracy era, the Indonesian Government experienced hyperinflation. Hyperinflation can occur due to the lack of supply of goods or surplus in market demand resulting in too fast growth in money circulation or instability in the amount of money in society. The Indonesian Government issued Presidential Decree No. 27 of 1965 concerning the issuance of new rupiah currency and the withdrawal of old rupiah currency to overcome hyperinflation or economic difficulties. This was implemented to avoid economic chaos and fraud. The sanering monetary policy initially made people panic, after that, the implementation of the sanering monetary policy could run safely, smoothly and under control because the Government of the Republic of Indonesia, especially the relevant institutions, continuously provided guidance to society.